Postoperative Venous Thromboembolism after Neurotologic Surgery - Ali, Noor-E-Seher; Alyono, Jennifer C.; Song, Yohan; Kouhi, Ali; Blevins, Nikolas H. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study aimed to determine the incidence of postoperative venous thromboembolism (VTE) in adults undergoing neurotologic surgery at a single center.Methods The records of adults undergoing neurotologic surgery from August 2009 to December 2016 at a tertiary care hospital were reviewed for VTE within 30 postoperative days. Particular attention was focused on postoperative diagnosis codes, imaging, and a keyword search of postoperative notes. Caprini risk scores were calculated.Results Among 387 patients, 5 experienced postoperative VTE including 3 cases of pulmonary embolism (PE) and 2 cases of isolated deep vein thrombosis (DVT). All patients were given sequential compression devices perioperatively, and none received preoperative chemoprophylaxis. Patients with Caprini score > 8 had a significantly higher rate of VTE compared with those < 8 (12.5 vs. 1%, p = 0.004). Receiver operating characteristic analysis revealed the Caprini risk assessment model to be a fair predictor of VTE, with a C-statistic of 0.70 (95% confidence interval [CI]: 0.49–0.92).Conclusion While no specific validated VTE risk stratification scheme has been widely accepted for patients undergoing neurotologic surgery, the Caprini score appears to be a useful predictor of risk. The benefits of chemoprophylaxis should be balanced with the risks of intraoperative bleeding, as well as the potential for postoperative intracranial hemorrhage.
Keywords: venous thromboembolism; deep venous thrombosis; pulmonary embolism; neurotologic surgery; Caprini score